2010
DOI: 10.1002/cne.22317
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin interneurons delineate the inner part of the external plexiform layer in the mouse main olfactory bulb

Abstract: Neuropeptides play a major role in the modulation of information processing in neural networks. Somatostatin, one of the most concentrated neuropeptides in the brain, is found in many sensory systems including the olfactory pathway. However, its cellular distribution in the mouse main olfactory bulb (MOB) is yet to be characterized. Here we show that approximately 95% of mouse bulbar somatostatin-immunoreactive (SRIF-ir) cells describe a homogeneous population of interneurons. These are restricted to the inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 103 publications
(149 reference statements)
7
66
0
Order By: Relevance
“…The reduced gamma power, after pharmacological blockade or genetic deletion of sst2 receptors, reveals the existence of a potent endogenous somatostatin tone on these receptors that may participate in the homeostasis of the reciprocal synapse by regulating synaptic transmission in mitral cells. In the MOB, sst2 receptors are mostly concentrated in the EPL and somatostatin is present in a subset of EPL interneurons (Lepousez et al, 2010) that receive high-frequency inputs from mitral cells (Hamilton et al, 2005). By analogy with hippocampal somatostatin-expressing cells during seizure (Vezzani and Hoyer, 1999;Baraban and Tallent, 2004), an elevated level of excitation of somatostatin interneurons induced by mitral cells may control peptide release that, in turn, would modulate the strength of the dendrodendritic synapse.…”
Section: Somatostatin Tone On Mitral Cell Sst2 Receptors In the Mobmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced gamma power, after pharmacological blockade or genetic deletion of sst2 receptors, reveals the existence of a potent endogenous somatostatin tone on these receptors that may participate in the homeostasis of the reciprocal synapse by regulating synaptic transmission in mitral cells. In the MOB, sst2 receptors are mostly concentrated in the EPL and somatostatin is present in a subset of EPL interneurons (Lepousez et al, 2010) that receive high-frequency inputs from mitral cells (Hamilton et al, 2005). By analogy with hippocampal somatostatin-expressing cells during seizure (Vezzani and Hoyer, 1999;Baraban and Tallent, 2004), an elevated level of excitation of somatostatin interneurons induced by mitral cells may control peptide release that, in turn, would modulate the strength of the dendrodendritic synapse.…”
Section: Somatostatin Tone On Mitral Cell Sst2 Receptors In the Mobmentioning
confidence: 99%
“…Neuropeptides, present in local interneurons and released after highfrequency stimulations (Vezzani and Hoyer, 1999;Baraban and Tallent, 2004), could act as intrinsic network modulators. In mice, the neuropeptide somatostatin is concentrated in a subset of external plexiform layer (EPL) interneurons (Lepousez et al, 2010). These interneurons receive high-frequency inputs from mitral cells (Hamilton et al, 2005), which provide a favorable context for peptide release.…”
Section: Introductionmentioning
confidence: 99%
“…SOM interneurons control local inhibition along dendritic glutamatergic domains through local direct or indirect disinhibition processes (Fino and Yuste, 2011;Pfeffer et al, 2013). SOM neurons were described in human OB (Bouras et al, 1986;Ohm et al, 1988) and in most olfactory centers in rodents (Brunjes et al, 2005(Brunjes et al, , 2011Eyre et al, 2009;Hwang et al, 2004;Lepousez et al, 2010a;Saiz-Sanchez et al, 2012;Shipley and Ennis, 1996), suggesting that the peptide participates to olfactory processing. Genetic and pharmacologic studies demonstrated that endogenous SOM transduction in the OB modulates local oscillations activity and fine discrimination in mice (Lepousez et al, 2010b).…”
Section: Discussionmentioning
confidence: 98%
“…In AD human cortex or cerebrospinal fluid samples as in experimental models, the decline of SOM levels is correlated with the progression of neuropathologic hallmarks (Ramos et al, 2006;Tan et al, 2010) and the extent of cognitive impairment (Andrews-Zwilling et al, 2010;Bierer et al, 1995;Grouselle et al, 1998;Perez-Cruz et al, 2011). SOM neurons have also been described in human and rodent OB (Bouras et al, 1987;Huang et al, 2013;Lepousez et al, 2010a;Ohm et al, 1988;Saiz-Sanchez et al, 2012) and olfactory cortex (Brunjes et al, 2005(Brunjes et al, , 2011Saiz-Sanchez et al, 2010, 2014Suzuki and Bekkers, 2009) together with SOM receptors (SSTR1 to SSTR4, Csaba and Dournaud, 2001;Lepousez et al, 2010a;Martel et al, 2012;Videau et al, 2003). Furthermore, in vivo manipulation of bulbar SSTR2 impacts both OB synaptic activity and olfactory acuity (Lepousez et al, 2010b), demonstrating that endogenous SOM contributes to olfactory processing.…”
Section: Introductionmentioning
confidence: 95%
“…Lepousez et al recently demonstrated that SST-immunoreactive interneurones interact directly with mitral cell dendrites, with the participation of dendrodendritic reciprocal synapses. This provides an anatomical basis for a neuromodulatory role of the peptide on the granule-mitral cell dendritic interactions that are fundamental to olfactory processing [17,18].…”
Section: Introductionmentioning
confidence: 99%